2008
DOI: 10.1021/jp801395h
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of Soret-Excited Tetrapyrroles in Solution. I. Metalloporphyrins: MgTPP, ZnTPP, and CdTPP

Abstract: The photophysical behavior of three Soret-excited diamagnetic meso-substituted tetraphenylmetalloporphyrins, MgTPP, ZnTPP, and CdTPP, have been examined in a wide variety of solvents using both steady-state and femtosecond fluorescence upconversion methods. The S 2 population of MgTPP decays to S 1 on the time scale of a few picoseconds with unit S 2-S 1 internal conversion efficiency, and the decay rates conform to the weak coupling case of radiationless transition theory. The energy gap law parameters charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
166
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(191 citation statements)
references
References 45 publications
25
166
0
Order By: Relevance
“…Soret emission is known to undergo a small Stokes shift and is thus limited to λ < 470 nm. 13,22 The broadband centred at about 580 nm appears as a mirror image of the Q band absorption which peaks at 510 nm and has a shoulder at 540 nm (see red dashed line, the absorption features at lower wavelengths were assigned to charge transfer bands 23 ). It is therefore, attributed to emission of the S 1 state.…”
Section: Is a Vibrationally Hot Ground State (Gs)mentioning
confidence: 99%
“…Soret emission is known to undergo a small Stokes shift and is thus limited to λ < 470 nm. 13,22 The broadband centred at about 580 nm appears as a mirror image of the Q band absorption which peaks at 510 nm and has a shoulder at 540 nm (see red dashed line, the absorption features at lower wavelengths were assigned to charge transfer bands 23 ). It is therefore, attributed to emission of the S 1 state.…”
Section: Is a Vibrationally Hot Ground State (Gs)mentioning
confidence: 99%
“…The presence of such a state has also been proposed experimentally. [26,29] The detailed composition and the character of the low-lying electronic states of Zn porphyrin, as well as a comparison with results obtained by using the time-dependent density functional theory are presented in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…[22,23] A considerable number of time-resolved studies of transient absorption, fluorescence, and photoionization have been conducted on ZnTPP both in ultracold supersonic jets [24,25] as well as in various organic solvents. [26] Most investigations focused on the dynamics induced by B band absorption and strived for revealing the various radiative and nonradiative relaxation processes, such as internal conversion from B to Q band, fluorescence from both bands, [27,28] as well as intersystem crossing to a manifold of triplet states, [26,29] eventually leading to phosphorescence. It has been found that the precise choice of the excitation wavelength can have a profound influence on the induced dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The time dependence of the anisotropy on the fs-timescale is governed by rearrangements in the excited state which can have drastic variations given how small geometry changes can interchange between GSB, SE and ESA as observed in the wavelength dependence of the zero time anisotropies. Moreover, the long-time constant about 65 ps show that about 30% excited molecules can undergo direct intersystem crossing to triplet manifold in CdTPP and suggest an additional relaxation pathway competing with ground state bleach [5,7]. Another possible or additional reason for the slow decay of the transient anisotropy could be attributed to the specific structure of CdTPP which is more rigid.…”
Section: Resultsmentioning
confidence: 99%